Quasielastic electron scattering on ⁶³Cu in the giant resonance energy region - Denyak, V.V.; Khvastunov, V.M.; Paschuk, S.A.; Schelin, H.R. (Вопросы атомной науки и техники, 2009)
The result of the extraction of the quasielastic part from the electron scattered spectra on ⁶³Cu is reported. The position of the peak maximum was determined for each quasielastic spectrum and the momentum transfer dependence of its shift with respect to the case of scattering on a free nucleon is presented in the momentum transfer range of q = 0.5...1.2 fm⁻¹. Представлено результат виділення квазіпружної частини перерізу з спектрів розсіяних на ⁶³Cu електронів. У кожному з отриманих квазіпружних спектрів визначено положення максимуму та представлено залежність зсуву його енергетичного положення відносно кінематики розсіяння на вільному нуклоні в диапазоні переданих імпульсів q = 0.5...1.2 фм⁻¹. Представлен результат выделения квазиупругой части сечения из спектров рассеянных на ⁶³Cu электронов. В каждом из полученных квазиупругих спектров определено положение максимума и представлена зависимость сдвига его энергетического положения относительно кинематики рассеяния на свободном нуклоне в диапазоне переданных импульсов q = 0.5...1.2 фм⁻¹.